The Bank Specific Determinants of Loan Growth and Stability: Evidence from Indonesia - Pananda Pasaribu; Bonnie Mindosa (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This study aims to examine the specific determinants of loan growth and the consequences of excessive loan growth on bank stability. Background Problems: Bank loans play an important role in economic growth, but previous studies indicate that excessive loans lead to bank instability. Novelty: This study undertakes a comprehensive analysis, as it will discuss both the loan determinants and excessive loans simultaneously. Research Methods: This study covers more than 89% of the total loans of commercial banks (listed and non-listed banks) between 2002 and 2018 and it employs GMM in order to obtain robust estimations. Finding/Results: The growth of customers’ deposits and gross NPL are the most important factors in explaining loan growth in Indonesia. Banks with excessive loans tend to have high levels of credit risk. Conclusion: Banks’ liquidity and credit risk have important roles in explaining banks’ loans. However, excessive loans could lead to bank instability, particularly for small banks.